Mutation Analysis of the Mitochondrial tRNA Genes in Iranian Coronary Atherosclerosis Patients - Mohammad Mehdi HEIDARI; Mahboobe DERAKHSHANI; Fatemeh SEDIGHI; Seyed Khalil FORUZAN-NIA (Tehran University of Medical Sciences, 2017)
Background: Atherosclerosis is a disease that affects large and medium size arteries in the body that underlies coronary heart disease. Several nucleotide changes in mitochondrial tRNA genes have been reported in various diseases. The purpose of the study was to identify hotspot mitochondrial tRNA mutations in atherosclerotic patients. Methods: In this case-control study, the variations of ten mitochondrial tRNA genes (about 50%) were investigated in 70 patients from October 2013 and June 2015 suffered from atherosclerosis. The related mitochondrial area was amplified using PCR methid. The mutation analysis was performed by Single Strand Conformational Polymorphism (SSCP) and Restriction Fragment Length Polymorphism (RFLP). All the positive samples were sequenced. Results: We found one novel heteroplasmic mutation (m.5725T>G) and three reported single nucleotide polymorphisms (SNPs) previously in other diseases including m.5568A>G, m.5711A>G and m.12308A>G. Conclusion: These tRNA mutations can alter their steady state level and affect the structure of tRNA. The role of mitochondrial tRNA mutations in the pathogenesis of atherosclerosis could potentially be important for the understanding of mitochondrial dysfunction in coronary atherosclerotic plaque formation.